Contrast Saline Mixture DualFlow Injection Protocols for Low-Kilovolt Computed Tomography Angiography: A Systematic Phantom and Animal Study. Issue 12 (December 2020) - Overhoff, Daniel; Jost, Gregor; McDermott, Michael; Wichtmann, Barbara; Schoenberg, Stefan O.; Pietsch, Hubertus; Attenberger, Ulrike
Abstract : Objective: The aim of this study was to evaluate a contrast media (CM)–saline mixture administration with DualFlow (DF) to adapt injection protocols to low-kilovolt (kV) computed tomography angiography (CTA). Materials and Methods: In both a circulation phantom and animal model (5 Goettingen minipigs), 3 injection protocols were compared in dynamic thoracic CTA: ( a ) DF injection protocol at 80 kV with a iodine delivery rate (IDR) of 0.9 gI/s, a flowrate of 5 mL/s injected with a 60%/40% ratio of iopromide (300 mgI/mL) and saline (dose contrast medium 180 mgI/kg body weight [BW]); ( b ) reference CTA was performed at 120 kV and a 40% higher iodine dose applied at higher IDR (1.5 gI/s, 5 mL/s iopromide [300 mgI/mL]; no simultaneously administered saline; 300 mgI/kg BW); and ( c ) conventional single-flow (SF) protocol with identical IDR as the DF protocol at 80 kV (0.9 gI/s, 3 mL/s iopromide [300 mgI/mL]; no simultaneously administered saline; 180 mgI/kg BW). All 3 injection protocols are followed by a saline chaser applied at the same flow rate as the corresponding CM injection. Time attenuation curves representing the vascular bolus shape were generated for pulmonary trunk and descending aorta. Results: In the circulation phantom, pulmonary and aortic time attenuation curves for the 80 kV DF injection protocols do not significantly differ from the 80 kV SF and the 120 kV SF reference. In the animal model, the 80 kV DF protocol shows similar pulmonal and aortic peak enhancement when compared with the 120 kV SF and 80 kV SF protocols. Also, the bolus length above an attenuation level of 300 HU reveals no significant differences between injection protocols. However, the time to peak was significantly shorter for the 80 kV DF when compared with the 80 kV SF protocol (15.78 ± 1.9 seconds vs 18.24 ± 2.0 seconds; P = 0.008). Conclusion: DualFlow injection protocols can be tailored for low-kV CTA by reducing the IDR while overall flow rate remains unchanged. Although no differences in attenuation were found, DF injections offer a shorter time to peak closer to the reference 120 kV protocol. This allows the use of DF injection protocols to calibrate bolus density in low-kV CTA and yields the potential for a more individualized CM administration.